Changes to vegetation structure and tree species composition drive bird species turnover following disturbance in southwestern United States mixed-conifer forest - Harrison Jones; Brandon Merriell; Megan Swan; Matthew Johnson; Rodney Siegel (Forest Ecology and Management, 2026)

The isotopic composition of solid-phase extracted dissolved organic nitrogen in seawater - Yeongjun Ryu; Dario Marconi; Sandi M. Smart; Sarah E. Fawcett; Rodney Johnson; Run Zhang; Angela N. Knapp; Sergey Oleynik; Alfredo Martínez-García; Gerald H. Haug; Daniel M. Sigman (Marine Chemistry, 2026)

Urban farms support cavity-nesting bees and DNA metabarcoding reveals weeds are key pollen resources - Katherine J. Turo; Rodney T. Richardson; Molly Frabotta; Reed M. Johnson; Mary M. Gardiner (Landscape and Urban Planning, 2026)

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Analysis of contaminant residues in honey bee hive matrices - Donna A. Glinski; S. Thomas Purucker; Jeffrey M. Minucci; Rodney T. Richardson; Chia-Hua Lin; Reed M. Johnson; W. Matthew Henderson (Science of The Total Environment, 2024)

Wildfire burn severity and stream chemistry influence aquatic invertebrate and riparian avian mercury exposure in forested ecosystems - Garth Herring; Lora B. Tennant; James J. Willacker; Matthew Johnson; Rodney B. Siegel; Julia S. Polasik; Collin A. Eagles-Smith (Ecotoxicology, 2024)

Forty years of ocean acidification observations (1983–2023) in the Sargasso Sea at the Bermuda Atlantic Time-series Study site - Nicholas R. Bates; Rodney J. Johnson (Frontiers in Marine Science, 2023)
Ocean physical and biogeochemical conditions are rapidly changing over time. Forty years of observations from 1983 to 2023 collected at the Bermuda Atlantic Time-series Study (BATS) site near Bermuda in the North Atlantic Ocean shows continuing trends of surface warming, increase in salinity, loss of dissolved oxygen (DO), increase in carbon dioxide (CO 2 ), and ocean acidification (OA) effects. Over this period, the ocean has warmed by about +1°C, increased in salinity by +0.136, and lost DO by 12.5 µmol kg −1 or ~6%. Since the 1980s, ocean dissolved inorganic carbon (DIC), total alkalinity (TA), a tracer of anthropogenic CO 2 (C TrOCA ), and fugacities/partial pressures of CO 2 (i.e., f CO 2 and p CO 2 ) have continued to increase substantially, with no evidence of a reduction in the rates of change over time. Contemporaneously, ocean pH has decreased by ~0.1 pH units [with ocean acidity (i.e., H + ) increasing by >30%], and the saturation states of calcium carbonate minerals (Ω calcite and Ω aragonite ) have decreased. These OA indicators show that the chemical conditions for calcification have become less favorable over the past 40 years. Updating of data and trends at the BATS site show how ocean chemistry of the 2020s is now outside the range observed in the 1980s, and how essential these data are for predicting the response of ocean chemistry and marine ecosystems to future shifting earth and ocean conditions.

Simulated nitrous oxide emissions from multiple agroecosystems in the U.S. Corn Belt using the modified SWAT-C model - Kang Liang; Junyu Qi; Xuesong Zhang; Bryan Emmett; Jane M.F. Johnson; Robert W. Malone; Glenn E. Moglen; Rodney T. Venterea (Environmental Pollution, 2023)

Ocean Observing in the North Atlantic Subtropical Gyre - Nicholas Bates; Rodney Johnson (Oceanography, 2021)

PAC1 Receptor Internalization and Endosomal MEK/ERK Activation Is Essential for PACAP-Mediated Neuronal Excitability - Victor May; Gregory C. Johnson; Sayamwong E. Hammack; Karen M. Braas; Rodney L. Parsons (Journal of Molecular Neuroscience, 2021)

Application of plant metabarcoding to identify diverse honeybee pollen forage along an urban–agricultural gradient - Rodney T. Richardson; Tyler D. Eaton; Chia‐Hua Lin; Garrett Cherry; Reed M. Johnson; Douglas B. Sponsler (Molecular Ecology, 2021)
Understanding animal foraging ecology requires large sample sizes spanning broad environmental and temporal gradients. For pollinators, this has been hampered by the laborious nature of morphologically identifying pollen. Identifying pollen from urban environments is particularly difficult due to the presence of diverse ornamental species associated with consumer horticulture. Metagenetic pollen analysis represents a potential solution to this issue. Building upon prior laboratory and bioinformatic methods, we applied quantitative multilocus metabarcoding to characterize the foraging ecology of honeybee colonies situated in urban, suburban, mixed suburban–agricultural and rural agricultural sites in central Ohio, USA. In cross‐validating a subset of our metabarcoding results using microscopic palynology, we find strong concordance between the molecular and microscopic methods. Our results suggest that forage from the agricultural site exhibited decreased taxonomic diversity and temporal turnover relative to the urban and suburban sites, though the generalization of this observation will require replication across additional sites and cities. Our work demonstrates the power of honeybees as environmental samplers of floral community composition at large spatial scales, aiding in the distinction of taxa characteristically associated with urban or agricultural land use from those distributed ubiquitously across the sampled landscapes. Observed patterns of high forage diversity and compositional turnover in our more urban sites are likely reflective of the fine‐grain heterogeneity and high beta diversity of urban floral landscapes at the scale of honeybee foraging. This provides guidance for future studies investigating how relationships between urbanization and measures of pollinator health are mediated by variation in floral resource dynamics across landscapes.

Evolutionary genomics of gypsy moth populations sampled along a latitudinal gradient - Christopher J. Friedline; Trevor M. Faske; Brandon M. Lind; Erin M. Hobson; Dylan Parry; Rodney J. Dyer; Derek M. Johnson; Lily M. Thompson; Kristine L. Grayson; Andrew J. Eckert (Molecular Ecology, 2019)
The European gypsy moth ( Lymantria dispar L.) was first introduced to Massachusetts in 1869 and within 150 years has spread throughout eastern North America. This large‐scale invasion across a heterogeneous landscape allows examination of the genetic signatures of adaptation potentially associated with rapid geographical spread. We tested the hypothesis that spatially divergent natural selection has driven observed changes in three developmental traits that were measured in a common garden for 165 adult moths sampled from six populations across a latitudinal gradient covering the entirety of the range. We generated genotype data for 91,468 single nucleotide polymorphisms based on double digest restriction‐site associated DNA sequencing and used these data to discover genome‐wide associations for each trait, as well as to test for signatures of selection on the discovered architectures. Genetic structure across the introduced range of gypsy moth was low in magnitude ( F ST = 0.069), with signatures of bottlenecks and spatial expansion apparent in the rare portion of the allele frequency spectrum. Results from applications of Bayesian sparse linear mixed models were consistent with the presumed polygenic architectures of each trait. Further analyses indicated spatially divergent natural selection acting on larval development time and pupal mass, with the linkage disequilibrium component of this test acting as the main driver of observed patterns. The populations most important for these signals were two range‐edge populations established less than 30 generations ago. We discuss the importance of rapid polygenic adaptation to the ability of non‐native species to invade novel environments.

Quantitative multi‐locus metabarcoding and waggle dance interpretation reveal honey bee spring foraging patterns in Midwest agroecosystems - Rodney T. Richardson; Hailey R. Curtis; Emma G. Matcham; Chia‐Hua Lin; Sreelakshmi Suresh; Douglas B. Sponsler; Luke E. Hearon; Reed M. Johnson (Molecular Ecology, 2019)
We explored the pollen foraging behaviour of honey bee colonies situated in the corn and soybean dominated agroecosystems of central Ohio over a month‐long period using both pollen metabarcoding and waggle dance inference of spatial foraging patterns. For molecular pollen analysis, we developed simple and cost‐effective laboratory and bioinformatics methods. Targeting four plant barcode loci (ITS2, rbcL , trnL and trnH ), we implemented metabarcoding library preparation and dual‐indexing protocols designed to minimize amplification biases and index mistagging events. We constructed comprehensive, curated reference databases for hierarchical taxonomic classification of metabarcoding data and used these databases to train the metaxa 2 DNA sequence classifier. Comparisons between morphological and molecular palynology provide strong support for the quantitative potential of multi‐locus metabarcoding. Results revealed consistent foraging habits between locations and show clear trends in the phenological progression of honey bee spring foraging in these agricultural areas. Our data suggest that three key taxa, woody Rosaceae such as pome fruits and hawthorns, Salix , and Trifolium provided the majority of pollen nutrition during the study. Spatially, these foraging patterns were associated with a significant preference for forests and tree lines relative to herbaceous land cover and nonflowering crop fields.

Urbanization as a facilitator of gene flow in a human health pest - Lindsay S. Miles; J. Chadwick Johnson; Rodney J. Dyer; Brian C. Verrelli (Molecular Ecology, 2018)
Urban fragmentation can reduce gene flow that isolates populations, reduces genetic diversity and increases population differentiation, all of which have negative conservation implications. Alternatively, gene flow may actually be increased among urban areas consistent with an urban facilitation model. In fact, urban adapter pests are able to thrive in the urban environment and may be experiencing human‐mediated transport. Here, we used social network theory with a population genetic approach to investigate the impact of urbanization on genetic connectivity in the Western black widow spider, as an urban pest model of human health concern. We collected genomewide single nucleotide polymorphism variation from mitochondrial and nuclear double‐digest RAD (ddRAD) sequence data sets from 210 individuals sampled from 11 urban and 10 nonurban locales across its distribution of the Western United States. From urban and nonurban contrasts of population, phylogenetic, and network analyses, urban locales have higher within‐population genetic diversity, lower between‐population genetic differentiation and higher estimates of genetic connectivity. Social network analyses show that urban locales not only have more connections, but can act as hubs that drive connectivity among nonurban locales, which show signatures of historical isolation. These results are consistent with an urban facilitation model of gene flow and demonstrate the importance of sampling multiple cities and markers to identify the role that urbanization has had on larger spatial scales. As the urban landscape continues to grow, this approach will help determine what factors influence the spread and adaptation of pests, like the venomous black widow spider, in building policies for human and biodiversity health.

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Soil Greenhouse Gas Emissions in Response to Corn Stover Removal and Tillage Management Across the US Corn Belt - Virginia L. Jin; John M. Baker; Jane M.-F. Johnson; Douglas L. Karlen; R. Michael Lehman; Shannon L. Osborne; Thomas J. Sauer; Diane E. Stott; Gary E. Varvel; Rodney T. Venterea; Marty R. Schmer; Brian J. Wienhold (BioEnergy Research, 2014)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Above‐ and belowground responses of arctic tundra ecosystems to altered soil nutrients and mammalian herbivory - Laura Gough; John C. Moore; Gauis R. Shaver; Rodney T. Simpson; David R. Johnson (Ecology, 2012)
Theory and observation indicate that changes in the rate of primary production can alter the balance between the bottom‐up influences of plants and resources and the top‐down regulation of herbivores and predators on ecosystem structure and function. The Exploitation Ecosystem Hypothesis (EEH) posited that as aboveground net primary productivity (ANPP) increases, the additional biomass should support higher trophic levels. We developed an extension of EEH to include the impacts of increases in ANPP on belowground consumers in a similar manner as aboveground, but indirectly through changes in the allocation of photosynthate to roots. We tested our predictions for plants aboveground and for phytophagous nematodes and their predators belowground in two common arctic tundra plant communities subjected to 11 years of increased soil nutrient availability and/or exclusion of mammalian herbivores. The less productive dry heath (DH) community met the predictions of EEH aboveground, with the greatest ANPP and plant biomass in the fertilized plots protected from herbivory. A palatable grass increased in fertilized plots while dwarf evergreen shrubs and lichens declined. Belowground, phytophagous nematodes also responded as predicted, achieving greater biomass in the higher ANPP plots, whereas predator biomass tended to be lower in those same plots (although not significantly). In the higher productivity moist acidic tussock (MAT) community, aboveground responses were quite different. Herbivores stimulated ANPP and biomass in both ambient and enriched soil nutrient plots; maximum ANPP occurred in fertilized plots exposed to herbivory. Fertilized plots became dominated by dwarf birch (a deciduous shrub) and cloudberry (a perennial forb); under ambient conditions these two species coexist with sedges, evergreen dwarf shrubs, and Sphagnum mosses. Phytophagous nematodes did not respond significantly to changes in ANPP, although predator biomass was greatest in control plots. The contrasting results of these two arctic tundra plant communities suggest that the predictions of EEH may hold for very low ANPP communities, but that other factors, including competition and shifts in vegetation composition toward less palatable species, may confound predicted responses to changes in productivity in higher ANPP communities such as the MAT studied here.

Development and Experimental Validation of a 20K Atlantic Cod (Gadus morhua) Oligonucleotide Microarray Based on a Collection of over 150,000 ESTs - Marije Booman; Tudor Borza; Charles Y. Feng; Tiago S. Hori; Brent Higgins; Adrian Culf; Daniel Léger; Ian C. Chute; Anissa Belkaid; Marlies Rise; A. Kurt Gamperl; Sophie Hubert; et al. (Marine Biotechnology, 2011)

Variations in Synechococcus cell quotas of phosphorus, sulfur, manganese, iron, nickel, and zinc within mesoscale eddies in the Sargasso Sea - Benjamin S. Twining; Daliangelis Nuñez-Milland; Stefan Vogt; Rodney S. Johnson; Peter N. Sedwick (Limnology and Oceanography, 2010)
The quotas of P, S, Mn, Fe, Ni, and Zn in individual Synechococcus cells collected from the surface and deep chlorophyll maximum (DCM) layer of three mesoscale eddies in the Sargasso Sea were measured using synchrotron X‐ray fluorescence microscopy. Cells in a mode‐water eddy had significantly higher P (57 ± 10 amol) and Mn (28 ± 7 zmol) cell quotas than cells collected from a cyclone (22 ±2 amol and 10 ± 1 zmol, respectively) or anticyclone (25 ± 3 amol and 18 ± 3 zmol, respectively). Conversely, Ni and Zn quotas were significantly higher in the cells from the anticyclone (92 ± 19 and 561 ± 150 zmol, respectively) than in cells from the cyclonic (25 ± 4 and 35 ± 7 zmol, respectively) or mode‐water (30 ± 9 and 21 ± 8 zmol, respectively) eddies. These changes may reflect biochemical responses (e.g., production of urease and alkaline phosphatase) to gradients in inorganic N and P supplies. Cellular quotas of Fe (111 ± 17 zmol in the cyclone) and S (52 ± 6 amol in the cyclone) did not vary significantly among eddies despite two‐ to threefold higher dissolved and particulate Fe concentrations in the anticylone. Cells collected from 10‐m depth contained approximately 80% more Ni and S than cells collected from the DCM, potentially reflecting cell responses to heightened oxidative stress. Depthrelated trends varied by eddy for the other elements. Cellular P and Zn varied significantly during repeated samplings of the cyclone, with quotas of both elements dropping as bulk chlorophyll biomass in the DCM increased. These data demonstrate the dynamic responses of phytoplankton elemental composition to physical and chemical environmental gradients.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Menopause in Free-Ranging Rhesus Macaques: Estimated Incidence, Relation to Body Condition, and Adaptive Significance - Rodney L. Johnson; Ellen Kapsalis (International Journal of Primatology, 1998)